THE EFFECT OF FACTORS ON TAX AVOIDANCE IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Heri Sukendar; Irwan Djaja; Viani Mettaya (Universitas Multimedia Nusantara, 2022)
Abstract - This study aims to examine and obtain empirical evidence about the effect of gender diversity, characteristics of executives, CEO narcissism, profitability, and firm size on tax avoidance in Indonesia public listed banking companies over the period 2015-2020. Using a purposive sampling method, the sample selected in this study is 83 samples. Multiple linear regression analysis examines the effect of independent variables on the dependent variable. This study shows that gender diversity and profitability have significant effects on tax avoidance. Meanwhile, the characteristics of executives, CEO narcissism, and firm size has no significant impact on tax avoidance. Keywords: Tax Avoidance; Gender Diversity; Characteristics of Executives; CEO Narcissism, Profitability; Firm Size